A global modelling program for co-rotating twin-screw extruders - Teixeira, Cristina (2010)
A global plasticating modeling software for twin screw extruders is presented. The program computes the evolution of pressure, average and maximum temperature, shear rate, viscosity, mechanical power consumption, degree of fill, residence time and mixing along a sequence of the various elements (conveying, left handed and kneading blocks) that are used to assemble a typical screw. Modeling is performed from hopper to die, considering solids conveying, melting and melt flow and takes into account the geometrical characteristics of each screw element. The effect of the operating conditions and screw geometry on the flow were compared with experimental data.